Westonci.ca offers fast, accurate answers to your questions. Join our community and get the insights you need now. Join our platform to connect with experts ready to provide precise answers to your questions in various areas. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
Answer:
2
Step-by-step explanation:
[tex] - 2b - ( - 7) = 11 \\ \\ - 2b + 7 = 11 \\ \\ - 2b = 11 - 7 \\ \\ - 2b = 4 \\ \\ b = \frac{4}{ 2} \\ \\ b = 2[/tex]
Hope it help you
Answer:
b = -2
Step-by-step explanation:
[tex] - 2b - ( - 7) = 11[/tex]
[tex] - 2b + 7 = 11[/tex]
[tex] - 2b + 7 - 7 = 11 - 7[/tex]
[tex] - 2b = 11 - 7[/tex]
[tex] - 2b = 4[/tex]
[tex]b = 4 \div( - 2) = - 4 \div 2 [/tex]
[tex]\boxed{\green{b = - 2}}[/tex]
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.